Development of Instructional Video Media in Increasing Sex Education Knowledge for Students with Hearing Impairment - Nur Latifah Hanum; Abdul Huda; Agung Kurniawan (Department of Special Education, 2018)
Students with hearing impairments need an instructional video media which can make them easier in understanding a theory about sex education especially menstruation. The aim of this study was to make a product which was instructional video media entitled “Cakap Hadapi Menstruasi”. The development of the product was adapted. The validation score from media experts was 96% (worthy to use). The validation score from material experts was 97% (worthy to use). Moreover, the result of the implementation showed the average score of students’ pre-test was 42 and post-test was 91. It means that the product was effective.